Controlling Internet of Things with different platforms: Security and Privacy challenges - et. al., Nora N. ALshehri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IOT) is one of the most important topics these days. It contains huge numbers of devices connected to each other with a very accurate access control through advanced and trusted control. IOT aims to use easy and achieve high security for the users. Based on that, this paper surveys recent research related to controlling three generations of network types have passed through the IOT which services the client in accessing or controlling their resources. In addition, this work aims to describe centralized framework (such as cloud computing), decentralized system (like edge computing), distributed network (Blockchain technology), and smart contract in IOT with the description of their security and privacy challenges